Regulatory aspects on the use of fish embryos in environmental toxicology - Halder, Marlies; Braunbeck, Thomas (Integrated environmental assessment and management, 2010)
Animal alternative tests are gaining serious consideration in an array of environmental sciences, particuarly as they relate to sound management of chemicals and wastewater discharges. The ILSI Health and Environmental Sciences Institute and the European Centre for Ecotoxicology and Toxicology of Chemicals (ECETOC) held an International Workshop on the Application of the Fish Embryo Test in March, 2008. This relatively young discipline is following advances in animal alternatives for human safety sciences, and it is advisable to develop a broad comparison of how animal alternative tests involving fish are viewed in a regulatory context over a wide array of authorities or advising bodies. These include OECD, Western Europe, North America, and Japan. This paper summarizes representative practices from these regions. Presently, the global regulatory environment has varying stances regarding the protection of fish for use as an experimental animal. Such differences have a long-term potential to lead to a lack of harmony in approaches to fish toxicity testing, especially for chemicals in commerce across multiple geographic regions. Implementation of alternative methods and approaches will be most successful if accepted globally, including methods of fish toxicity testing. An important area for harmonization would be in the interpretation of protected and nonprotected life stages of fish. Use of fish embryos represent a promising alternative and allow bridging to more technically challenging alternatives with longer prospective timelines, including cell-based assays, ecotoxicogenomics, and QSARs.